Ureteric stenting vs not stenting following uncomplicated ureteroscopic lithotripsy: A prospective randomised trial - Al Demour, Saddam (Arab J Urol, 2020)
OBJECTIVE: To compare three groups of patients who underwent uncomplicated ureteroscopic lithotripsy (URSL) and to evaluate whether stenting could be eliminated after the procedure, as there is no consensus about whether a ureteric stent should be placed after uncomplicated ureteroscopy for stone retrieval. PATIENTS AND METHODS: In this randomised clinical trial (NCT04145063) 105 patients underwent uncomplicated URSL for ureteric stones. They were prospectively randomised into three groups: Group 1 (34 patients) with a double pigtail ureteric stent, Group 2 (35 patients) with a double pigtail ureteric stent with extraction string, and Group 3 (36 patients) with no ureteric stent placed after the procedure. The outcomes measured were: postoperative visual analogue scale (VAS) score for flank pain and dysuria score, urgency, frequency, suprapubic pain, haematuria, analgesia requirement, operative time, re-hospitalisation, and return to normal physical activity. RESULTS: The mean (SD) operative time was significantly longer in groups 1 and 2 compared to Group 3, at 22.2 (9.1), 20.2 (6) and 15.1 (7.1) min, respectively (P < 0.001). The results of the VAS for flank pain and dysuria scores, urgency, frequency, haematuria, and suprapubic pain showed a significant difference at all time-points of follow-up, being significantly higher in groups 1 and 2 compared to Group 3 (all P < 0.001). Further analysis showed that measured outcomes, and analgesia need for groups 1 and 2 were similar, at all time-points except at week 1 and 1 month where Group 2 patients’ had less symptoms (P < 0.001). CONCLUSION: Double pigtail ureteric stent placement appears to be unnecessary in procedures considered ‘uncomplicated’ by operating urologists during surgery. The advantages of the double pigtail ureteric stent with extraction string over the double pigtail ureteric stent only include earlier and easier removal with earlier relief of symptoms, and less analgesia requirements. ABBREVIATIONS: KUB: plain abdominal radiograph of the kidneys, ureters and bladder; URSL: ureteroscopic lithotripsy; VAS: visual analogue scale